Phylogenetic diversity of culturable fungi in the Heshang Cave, central China - Man, Baiying; Wang, Hongmei; Xiang, Xing; Wang, Ruicheng; Yun, Yuan; Gong, Linfeng (Frontiers in Microbiology, 2015)
Caves are nutrient-limited and dark subterranean ecosystems. To date, attention has been focused on geological research of caves in China, whilst indigenous microbial diversity has been insufficiently characterized. Here, we report the fungal diversity in the pristine, oligotrophic, karst Heshang Cave, central China, using a culture-dependent method coupled with the analysis of the fungal rRNA-ITS gene sequences. A total of 194 isolates were obtained with six different media from 14 sampling sites of sediments, weathered rocks and bat guanos. Phylogenetic analysis clustered the 194 sequenced isolates into 33 genera within 15 orders of 3 phyla, Ascomycota, Basidiomycota and Zygomycota, indicating a high degree of fungal diversity in the Heshang cave. Notably, 16 out of the 36 fungal genera were also frequently observed in solution caves around the world and 23 genera were previously found in carbonate cave, indicating potential similarities among fungal communities in cave ecosystems. However, 10 genera in this study were not reported previously in any solution caves, thus expanding our knowledge about fungal diversity in cave ecosystems. Moreover, culturable fungal diversity varied from one habitat to another within the cave, being the highest in sediments, followed by weathered rocks and bat guanos as indicated by alpha-diversity indexes. At the genus level, Penicillium accounted for 40 %, 54 % and 52 % in three habitats of sediments, weathered rocks and bat guanos respectively. Trichoderma, Paecilomyces and Aspergillus accounted for 9 %, 22 % and 37 % in the above habitats, correspondingly. Despite of the dominance of Penicillium in all samples beta-diversity index indicated significant differences between each two fungal communities in the three habitats in view of both the composition and abundance. Our study is the first report on fungal communities in a natural pristine solution cave system in central China and sheds light on fungal diversity and functions in cave ecosystems.